The World Business Council for Sustainable Development develops new metrics for climate-smart agriculture to guide global corporate productivity, resilience and mitigation commitments for 2030. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Building on CCAFS contributions, the World Business Council for Sustainable Development launched new metrics for climate smart agriculture providing guidance to the corporate value chains to operationalize and track progress of their climate action commitments. Use of this guidance contributes to the 2030 targets of reducing greenhouse gas emissions from agriculture and land use change by 50%, making 50% more nutritious food available and strengthening the climate resilience of agricultural landscapes and farming communities through agro ecological approaches globally.